Chemogenetic activation of PVN CRH neurons disrupts the estrous cycle and LH dynamics in female mice - Yu, Junru; Li, Xiao-Feng; Tsaneva-Atanasova, Krasimira; Zavala, Eder; O’Byrne, Kevin T. (Frontiers in Endocrinology, 2024)
The impact of stress on reproductive function is significant. Hypothalamic paraventricular nucleus (PVN) corticotrophin-releasing hormone (CRH) plays a major role in regulating the stress response. Understanding how the hypothalamic-pituitary-adrenal (HPA) axis and the hypothalamic-pituitary-gonadal (HPG) axis interact is crucial for comprehending how stress can lead to reproductive dysfunction. However, whether stress influences reproductive function via modulating PVN CRH or HPA sequelae is not fully elucidated. In this study, we investigated the impact of chemogenetic activation of PVN CRH neurons on reproductive function. We chronically and selectively stimulated PVN CRH neurons in female CRH-Cre mice using excitatory designer receptor exclusively activated by designer drugs (DREADDs) viral constructs, which were bilaterally injected into the PVN. The agonist compound-21 (C21) was delivered through the drinking water. We determined the effects of DREADDs activation of PVN CRH neurons on the estrous cycles, LH pulse frequency in diestrus and metestrus and LH surge in proestrus mice. The effect of long-term C21 administration on basal corticosterone secretion and the response to acute restraint stress during metestrus was also examined. Additionally, computer simulations of a mathematical model were used to determine the effects of DREADDs activation of PVN CRH neurons, simulating chronic stress, on the physiological parameters examined experimentally. As a result, and consistent with our mathematical model predictions, the length of the estrous cycle was extended, with an increase in the time spent in estrus and metestrus, and a decrease in proestrus and diestrus. Additionally, the frequency of LH pulses during metestrus was decreased, but unaffected during diestrus. The occurrence of the preovulatory LH surge during proestrus was disrupted. The basal level of corticosterone during metestrus was not affected, but the response to acute restraint stress was diminished after long-term C21 application. These data suggest that PVN CRH neurons play a functional role in disrupting ovarian cyclicity and the preovulatory LH surge, and that the activity of the GnRH pulse generator remains relatively robust during diestrus but not during metestrus under chronic stress exposure in accordance with our mathematical model predictions.